Perancangan Animasi Interaktif Pengetahuan Dasar Bahaya Narkoba - Enuk Tuti Alawiah (SYNTAX Jurnal Informatika)
Interactive learning media is one of the popular methods that are used today.Interactive animations easier for students in the learning process so that it can absorbknowledge better. The design of interactive animations have basic knowledge of thedangers of drugs meant for the primary school level students to more easily understandthe basic knowledge of the dangers of drugs to health, to determine the shape and typeof drug and its effects on human health. The development method used is the waterfallmodel (Rosa Shalahudin 2014: 28). Results from this study is the design of interactiveanimation is easier for users to know and knowing the types of narcotics andpsychotropic substances, and know the dangers inherent in it. Results from testing of theuser is that students can better understand the material provided by the method oflearning interesting and interactive.